Switzerland's Apology for Compulsory Government-Welfare Measures: A Social Justice Turn? - Baer, Ursula M. (Social justice, 2016)
This article offers some insights into the history of historical compulsory government-welfare measures and the issue of children and youth in state care. It introduces a barely known history (Switzerland's compulsory government-welfare measures) and analyzes the content of the official apology Switzerland offered in 2013 to the victims of such measures. By focusing in particular on the history that warranted the apology and the terminology used in the apology itself, this article seeks to contribute to a new interdisciplinary field of study devoted to the long and diverse international history of (former) children and youth in "care" who were un-familied through compulsory measures informed by heterosexual, patriarchal, and racial norms.